Multi-analyte profiling in human carotid atherosclerosis uncovers pro-inflammatory macrophage programming in plaques - Shalhoub, Joseph; Viiri, Leena E.; Cross, Amanda J.; Gregan, Scott M.; Allin, David M.; Astola, Nagore; Franklin, Ian J.; Davies, Alun H.; Monaco, Claudia (Thrombosis and Haemostasis, 2016)
Molecular characterisation of vulnerable atherosclerosis is necessary for targeting functional imaging and plaque-stabilising therapeutics. Inflammation has been linked to atherogenesis and the development of high-risk plaques. We set to quantify cytokine, chemokine and matrix metalloproteinase (MMP) protein production in cells derived from carotid plaques to map the inflammatory milieu responsible for instability. Carotid endarterectomies from carefully characterised symptomatic (n=35) and asymptomatic (n=32) patients were enzymatically dissociated producing mixed cell type atheroma cell suspensions which were cultured for 24 hours. Supernatants were interrogated for 45 analytes using the Luminex 100 platform. Twenty-nine of the 45 analytes were reproducibly detectable in the majority of donors. The in vitro production of a specific network of mediators was found to be significantly higher in symptomatic than asymptomatic plaques, including: tumour necrosis factor α, interleukin (IL) 1β, IL-6, granulocytemacrophage colony-stimulating factor (GM-CSF), macrophage colonystimulating factor (M-CSF), CCL5, CCL20, CXCL9, matrix metalloproteinase (MMP)-3 and MMP-9. Ingenuity pathway analysis of differentially expressed analytes between symptomatic and asymptomatic patients identified a number of key biological pathways (p > 10–25). In conclusion, the carotid artery plaque culprit of ischaemic neurological symptoms is characterised by an inflammatory milieu favouring inflammatory cell recruitment and pro-inflammatory macrophage polarisation.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Atherosclerosis; carotid stenosis; inflammation; cytokines